AI for Our Planet: How Artificial Intelligence can Solve Global Challenges - Hemachandran, K.; Villamarin Rodriguez, Raul; Rincon, Manuel; Joshi, Himanshu; Acereda, Alberto (Bentham Science Publishers, 2026)
AI for Our Planet: How Artificial Intelligence Can Solve Global Challenges brings together insights from leading scholars and industry experts to examine the responsible and strategic use of AI in addressing pressing global challenges, including climate change, resource scarcity, environmental degradation, ethical governance, and socio-economic inequality. Across sixteen multidisciplinary chapters, the book positions AI not only as a transformative technological tool but also as a framework for building a sustainable and equitable future. Featuring real-world case studies on AI-driven governance, ethical and regulatory frameworks, climate diplomacy, circular economies, renewable energy, and sustainable resource management, the book offers forward-looking insights into AI's expanding global impact. Key Features Multidisciplinary perspectives integrating AI, sustainability, governance, and public policy Evidence-based discussions supported by real-world case studies Coverage of ethical, regulatory, and responsible AI deployment framework Practical insights into AI applications for climate action, resource management, and circular economy models Forward-looking analysis of AI's role in global development and environmental stewardship.